Biometric Recognition 7th Chinese Conference, CCBR 2012, Guangzhou, China, December 4-5, 2012. Proceedings - Zheng, Wei-Shi.; Sun, Zhenan; Wang, Yunhong; Chen, Xilin; Yuen, Pong C.; Lai, Jianhuang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 7th Chinese Conference on Biometric Recognition, CCBR 2012, held in Guangzhou, China, in December 2012. The 46 revised full papers were carefully reviewed and selected from 80 submissions. The papers address the problems in face, iris, hand biometrics, speaker, handwriting, gait, soft biometrics, security and other related topics, and contribute new ideas to research and development of reliable and practical solutions for biometric authentication.
Patch-Based Bag of Features for Face Recognition in Videos -- Fusion of Local Features for Face Recognition by Multiple Least Square Solutions -- Complete Gradient Face: A Novel Illumination Invariant Descriptor -- A Face Authentication Scheme Based on Affine-SIFT(ASIFT) and Structural Similarity (SSIM) -- A Study on the Effective Approach to Illumination-Invariant Face Recognition Based on a Single Image -- Weighted Group Sparse Representation Based on Robust Regression for Face Recognition -- 3D Face Pose Estimation Based on Multi-template AAM -- 3D Aided Face Recognition across Pose Variations -- Comparing Studies of Learning Methods for Human Face Gender Recognition -- Fusion of mSSIM and SVM for Reduced-Reference Facial Image Quality Assessment -- A Survey of Face Hallucination -- Active Shape Model Based on Sparse Representation -- On the Influence of Fingerprint Area in Partial Fingerprint Recognition -- Fingerprint Identification Based on Semi-supervised FSS -- A Performance Improvement Method for Existing Fingerprint Systems -- The Location Method of the Main Hand-Shape Feature Points -- Palmprint Feature Extraction Based on Improved Gabor Wavelet Combing LBP Operator -- The Research of Multi-spectral Hand Texture Fusion Method under a Non-constraint Condition -- Rotation Invariant Finger Vein Recognition -- Hand Dorsal Vein Recognition Based on Hierarchically Structured Texture and Geometry Features -- Hand Vein Recognition Based on Feature Coding -- Contact-Less Palm Vein Recognition Based on Wavelet Decomposition and Partial Least Square -- Iris Image Deblurring Based on Refinement of Point Spread Function -- Super Resolution Reconstruction and Recognition for Iris Image Sequence -- Fusion of Iris and Periocular Biometrics for Cross-Sensor Identification -- A Review of Advances in Iris Image Acquisition System -- 3D Pure Ear Extraction and Recognition -- Multimodal Ear Recognition Based on 2D+3D Feature Fusion -- Toward Emotional Speaker Recognition: Framework and Preliminary Results -- Orthogonal Subspace Combination Based on the Joint Factor Analysis for Text-Independent Speaker Recognition -- Exploration of Phase and Vocal Excitation Modulation Features for Speaker Recognition -- Cross-View Action Recognition Based on Statistical Machine Translation -- A Comparative Study of Several Feature Extraction Methods for Person Re-identification -- Improving Biometric Verification Systems by Fusing Z-norm and F-norm -- Biometric Identification System$1 (Bs Performance Enhancement by Improving Registration Progress -- Ethnicity Classification Based on a Hierarchical Fusion -- An Algorithm for Retina Features Extraction Based on Position of the Blood Vessel Bifurcation -- Recognition of Petechia Tongue Based on LoG and Gabor Feature with Spatial Information -- Human Age Estimation Using Ranking SVM -- Distance Entropy as an Information Measure for Binary Biometric Representation -- Kernel Sparse Locality Preserving Canonical Correlation Analysis for Multi-modal Feature Extraction -- Kernel Based Enhanced Maximum Margin Criterion for Feature Extraction -- A Novel Variance Minimization Segmentation Model -- Robust Integrated Locally Linear Embedding -- Estimating the Total Variability Space Using Sparse Probabilistic Principal Component Analysis -- A Competitive Model for Semi-supervised Discriminant Analysis.s
Keywords: Computer science; Computer software; Computer graphics; Computer vision; Optical pattern recognition; Biometrics; Computer Science; Biometrics; Pattern Recognition; Image Processing and Computer Vision; Algorithm Analysis and Problem Complexity; Computer Graphics; Information Systems Applications (incl. Internet).